Profitability, Liquidity, Solvability and Financial Distress: The Impact on Firm Value? Case Study of Various Industrial Sector Companies, Tbk 2018-2020 - Panglipursari, Dwi Lesno; Mardiana, Fitra; Gondokusumo, Ifan (JURNAL EKBIS, 2023)
This study aims to examine and analyze the effect of profitability, liquidity and solvency on financial distress and their impact on firm value both directly and indirectly in companies in the various industrial sectors of Tbk for the 2018 – 2020 period. The type of research used in this research is explanatory research (explanatory research) using a quantitative approach. The technique used in taking the sample is purposive sampling method, obtained a sample of 34 companies from a total population of 53 companies. The type of data used is secondary data. Data analysis was performed using descriptive statistics and inferential statistics using the SmartPLS tool. The results showed that the profitability variable proxied by ROE had a negative and significant effect on firm value, the profitability proxied by ROA had no effect on firm value. Liquidity and solvency have a negative and insignificant effect on firm value, while financial distress has a positive but not significant effect on firm value. Liquidity has a positive and significant effect on financial distress, while profitability and solvency have a positive but not significant effect on financial distress. Profitability, liquidity and solvency through financial distress have no significant effect on firm value.